(untitled) (Medicine Today, 2014)
A clinical trial was carried out in the department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka to evaluate the efficacy of Mometasone Furoate 0.1% cream in atopic dermatitis. Forty patients of atopic dermatitis were selected and randomized into two groups. In Group I, study patients were applied Mometasone Furoate 0.1% cream to the affected skin and in Group II, control patients were allowed to apply white vaseline to the affected skin. SCORAD index was assessed fortnightly at 2nd and 3rdvisit and final SCORAD index were calculated at the end of 4 week (3rd visit). In the study, at base line SCORAD index in case group was 49.76 ± 17.25 and in control group was 55.25 ± 13.94 (p>0.05). At 2nd visit that is at the end of 2 (two) weeks of medication SCORAD in case group was 27.39 ± 11.16 and in control group was 50.05 ± 14.69 (p=0.001) and at 3rd visit that is at the end of 4 (four) weeks of medication in case group SCORAD was 12.08 ± 6.87 and in control group was 46.70 ± 14.80 (p=0.001). Percent of reduction of SCORAD from 1st visit to 3rd visit in case group was 76.70 ± 8.10 and in control group was 16.88 ± 8.70 (p=0.001) which indicates satisfactory improvement and statistically significant. It can be concluded that once daily application of mometasone furoate 0.1% cream is effective in atopic dermatitis. DOI: http://dx.doi.org/10.3329/medtoday.v26i1.21311 Medicine Today 2014 Vol.26(1): 36-40